The Concept of "Kampus Merdeka" in Accordance with Freire's Critical Pedagogy - Binar Kurnia Prahani; Utama Alan Deta; Mochammad Yasir; Sri Astutik; Paken Pandiangan; Sayidah Mahtari; Husni Mubarok (Studies in Philosophy of Science and Education, 2020)
The Kampus Merdeka lately becomes the center of attention for the education circle in Indonesia. The government via Indonesian Minister of education and culture believed that the Kampus Merdeka as an effort to freedom for the education system more supportive of students and lecturers in achieving quality learning meaningful to face the disruption of the current era. This paper presents the authors' views on "Kampus Merdeka" which was promoted by the Indonesian government. Also, the authors will underline the concept of "Kampus Merdeka" in accordance with Paulo Freire's critical pedagogy. From our point of view, we give a position this concept is developed based on the thinking of Paulo Freire. As we know, Freire's educational model offered a model of education for freedom. In this case, the term ‘freedom’ means a transformation in a real system that is competitively related and complex.